2020
DOI: 10.1002/jbmr.4429
|View full text |Cite
|
Sign up to set email alerts
|

PTH and FGF23 Exert Interdependent Effects on Renal Phosphate Handling: Evidence From Patients With Hypoparathyroidism and Hyperphosphatemic Familial Tumoral Calcinosis Treated With Synthetic Human PTH 1–34

Abstract: Parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23) both influence blood phosphate levels by regulating urinary phosphate reabsorption. Clinical data suggest that adequate renal phosphate handling requires the presence of both FGF23 and PTH, but robust evidence is lacking. To investigate whether the phosphaturic effects of PTH and FGF23 are interdependent, 11 patients with hypoparathyroidism, which features high blood phosphate in spite of concomitant FGF23 elevation, and 1 patient with hyperphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Although, cFGF23 has remained mildly elevated, iFGF23 was normal. As recently described, both PTH and FGF23 independently lower TmP/GFR but both are required for normalcy of renal phosphate handling ( McKenna et al, 2021 ; Ovejero et al, 2021 ). It is possible that residual secondary hyperparathyroidism in case 1 accounts for lowering of TmP/GFR rather than residual tumor.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although, cFGF23 has remained mildly elevated, iFGF23 was normal. As recently described, both PTH and FGF23 independently lower TmP/GFR but both are required for normalcy of renal phosphate handling ( McKenna et al, 2021 ; Ovejero et al, 2021 ). It is possible that residual secondary hyperparathyroidism in case 1 accounts for lowering of TmP/GFR rather than residual tumor.…”
Section: Discussionmentioning
confidence: 73%
“…Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome, which is associated with phosphaturic mesenchymal tumors (PMT), resulting in an acquired form of severe chronic hypophosphatemia that leads to osteomalacia in adults ( Ryan et al, 1984 ; Minisola et al, 2017 ). Most cases are caused by excess tumoral production of fibroblast growth factor 23 (FGF23), one of the factors that regulates phosphate excretion ( McKenna et al, 2021 ; Ovejero et al, 2021 ). Increased circulating FGF23 in TIO inhibits sodium-dependent phosphate co-transporters (NaPi2a) on the luminal surface of the proximal renal tubule, which results in reduced phosphate reabsorption.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between FGF23 and PTH on the phosphaturic effect is unclear at present. A recent clinical study concluded that the phosphaturic effects of FGF23 and PTH were interdependent, with both required to adequately regulate renal phosphate handling ( 18 ). The authors showed that the administration of human PTH 1-34 normalized the serum phosphate level, followed by a significant decrease in FGF23 in 11 patients with hypoparathyroidism, which is characterized by a high serum phosphate level despite concomitant FGF23 elevation ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical study concluded that the phosphaturic effects of FGF23 and PTH were interdependent, with both required to adequately regulate renal phosphate handling ( 18 ). The authors showed that the administration of human PTH 1-34 normalized the serum phosphate level, followed by a significant decrease in FGF23 in 11 patients with hypoparathyroidism, which is characterized by a high serum phosphate level despite concomitant FGF23 elevation ( 18 ). Furthermore, two cases of XLH with tertiary hyperparathyroidism were reported to have a normalized TmP/GFR upon being rendered hypoparathyroidism by total parathyroidectomy but still showed the marked elevation of FGF23 ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…FGF-23 is elevated by chronic hyperphosphatemia [ 30 ]. A very recent and well-conducted clinical study [ 31 ] has shed light on the interdependent physiology of PTH and FGF-23 in patients with hypoparathyroidism. Since both FGF-23 and PTH are phosphaturic hormones, it was anticipated that patients with hypoparathyroidism, treated with synthetic human PTH (1-34), would serve as an optimal model to clarify which of either hormone would have a prominent role over the other in determining phosphate excretion.…”
Section: Phosphate In Hypoparathyroidismmentioning
confidence: 99%